2014
DOI: 10.1111/mpp.12112
|View full text |Cite
|
Sign up to set email alerts
|

Hexanoic acid protects tomato plants against Botrytis cinerea by priming defence responses and reducing oxidative stress

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 67 publications
3
84
0
Order By: Relevance
“…In the current study, pathogen-induced accumulation of H 2 0 2 was delayed in the mutants compared to the WT backgrounds without affecting the basal resistance to B. cinerea, showing that H 2 O 2 is not involved in basal resistance. However, at an early infection stage, the oxidative burst has a central role in priming plant resistance against necrotrophic pathogens such as B. cinerea (Aranega Bou et al 2014;Finiti et al 2014). In the current study, the accumulation of H 2 O 2 at different time points post inoculation in the tomato leaves followed a process that was similar to that described in earlier works, i.e., H 2 O 2 generally accumulated until 14 h after infection and in most cases did not further accumulate at later evaluation times.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, pathogen-induced accumulation of H 2 0 2 was delayed in the mutants compared to the WT backgrounds without affecting the basal resistance to B. cinerea, showing that H 2 O 2 is not involved in basal resistance. However, at an early infection stage, the oxidative burst has a central role in priming plant resistance against necrotrophic pathogens such as B. cinerea (Aranega Bou et al 2014;Finiti et al 2014). In the current study, the accumulation of H 2 O 2 at different time points post inoculation in the tomato leaves followed a process that was similar to that described in earlier works, i.e., H 2 O 2 generally accumulated until 14 h after infection and in most cases did not further accumulate at later evaluation times.…”
Section: Discussionmentioning
confidence: 99%
“…Hexanoic acid IR has been studied on both the transcriptomic and metabolic levels in tomato in relation to its protective effect against B. cinerea [12,139]. A marked metabolic reprogramming was associated with resistance triggered by hexanoic acid where several citrate and other primary metabolites were down-regulated.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…These results suggested that ROS accumulation and LCD do favor tissue colonization by necrotrophs. Other reports, however, have shown that the relationship between HR induction, ROS build‐up and decreased resistance to necrotrophs is more intricate than was anticipated, and cannot be taken as a general rule (Malolepsza and Urbanek, ; Unger et al ., ; Finiti et al ., ).…”
Section: Introductionmentioning
confidence: 97%